Islamic Business Ethics in Saudi Tourism: The Mediating Role of Spiritual Satisfaction in Driving Loyalty and Profitability - Abdelhai Abdelghani, Abdelrahman Ahmed; Mokhtar Ahmed, Hebatallah Ahmed (CV. SPDF Harmony, 2025)
Background: Saudi Arabia’s Vision 2030 positions tourism as a key economic pillar, emphasizing Sharīʿa-compliant services. Despite rapid investment, the ethical–spiritual nexus in tourism remains underexplored, particularly regarding the role of Islamic Business Ethics (IBE) in shaping customer experience and financial outcomes. Aims: This study investigates whether spiritual satisfaction and perceived value act as mediators between Islamic Business Ethics, customer loyalty, and profitability, while also examining religiosity as a moderating factor. Methods: A cross-sectional survey of 385 tourists in Saudi Arabia (November 2024–February 2025) was conducted using validated measurement scales. Structural equation modeling and the Hayes PROCESS macro were employed to test direct, indirect, and moderating effects. Result: A Findings reveal that IBE significantly enhances spiritual satisfaction (β = 0.582, p < 0.001) and profitability (β = 0.298, p < 0.001). Both spiritual satisfaction and perceived value partially mediated the link between IBE and customer loyalty, with explained variance in loyalty reaching 62.4%. Moreover, religiosity amplified the relationship between IBE and spiritual satisfaction, indicating stronger effects among highly religious guests. Conclusion: Islamic business ethics drive spiritual satisfaction and loyalty while contributing to profitability in Saudi Arabia’s hospitality sector. For managers, authentic ethical practices—especially when tailored to the needs of highly religious consumers—can yield deeper guest connections and long-term financial sustainability, aligning with the ambitions of Vision 2030.